N13 Living in rural communities with Inflammatory Bowel Disease: Perspectives on healthcare use and access to care from patients and providers in one Canadian province. (27th May 2021) - Rohatinsky, N; Russell, B; Boyd, I; Dickson, A; Fowler, S; Peña-Sánchez, J N; Quintin, C L; Risling, T; Wicks, K; Wicks, M
Abstract: Background: Living with Inflammatory Bowel Disease (IBD) requires lifelong, repeated interactions with the healthcare system. Individuals with IBD living in rural areas are often disadvantaged with limited access to IBD-related healthcare services in their local communities which can result in poor health outcomes. Furthermore, these individuals encounter additional out of pocket expenses to travel to urban centres for care. There is limited information about the experiences of access to IBD-related care from the perspectives of patients and providers living in rural communities. The purpose of this study was to examine healthcare utilization and access to care in individuals with IBD who reside in rural areas within one Canadian province. Methods: The qualitative results from a larger patient-oriented, mixed methods study will be reported. Seventeen individuals residing in rural communities from one Canadian province were recruited to participate. Fourteen individuals living with IBD and three healthcare providers were interviewed and shared their experiences on IBD-related access to care and healthcare use. Data was collected prior to the pandemic. Interview data was analyzed using thematic analysis to identify common themes. Results: Many participants identified access to care challenges associated with living in rural communities. Communication, stressors and support systems, and coordination of care were identified as themes. Participants described disconnects in communication with and between healthcare providers. They suggested virtual technology was underutilized and was a cost-effective means to enhance communication. Participants experienced feelings of isolation and identified stressors while living in rural areas. They recommended the integration of formal and informal supports to ease stressors and promote mental well-being. Participants reported gaps in care and described a lack of accessible, multidisciplinary rural healthcare providers to optimize their IBD-related care and health outcomes. This lack of access to rural care resulted in frequent travel to access a variety of services. Recruitment and retention of rural care providers was identified as a strategy to enhance access to care. Conclusion: Participants offered many suggestions to improve rural IBD-related care access within the healthcare system. These initiatives have great potential to increase quality of care, enhance quality of life, and reduce health system costs.